Checklist of Tunisian Cerceris Latreille, 1802 (Hymenoptera: Crabronidae: Philanthinae) with new country and provincial records. (2nd October 2021) - Ben Khedher, Hassib; Yıldırım, Erol; Braham, Mohamed
ABSTRACT: The fauna of Tunisian Cerceris Latreille, 1802 is summarised. It is presented by a total of 42 species and subspecies and an unidentified taxon. Among them, Cerceris clytia de Beaumont, 1959, C. dispar Dahlbom, 1845, C. flavilabris (Fabricius, 1793), C. priesneri Mochi, 1938 and C. quadricincta segregata de Beaumont, 1970 are reported for the first time in Tunisia. The knowledge of the genus is well-developed by new provincial records for all newly identified species excluding C. chromatica Schletterer, 1887 and C. nitrariae Morice, 1911.